2019
DOI: 10.3390/d11050076
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Gonadal Tissue to Validate Size at Reproductive Maturity in Kemp’s Ridley Sea Turtles Found Stranded in Texas, USA

Abstract: The Kemp’s ridley, Lepidochelys kempii, is the most endangered sea turtle in the world. Anthropogenic mortality of Kemp’s ridleys has been well documented in the Gulf of Mexico (GOM), USA. We evaluated the reproductive maturity of 75 Kemp’s ridley sea turtles found dead on GOM beaches on Mustang Island and North Padre Island, Texas, USA, 1994–1999. Straight carapace length (SCL) ranged from 40.8 to 68.7 cm. Preserved gonads and associated tissues were examined and measured. Gonadal measurements were then compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Of the 10 juvenile turtles (45.5%; SCL mean ± SD: 42.9 ± 12.6 cm, range: 26.7–59.0 cm), two were determined to be females based on visual examination of gonads at necropsy, and sex was undetermined in eight. The remaining 12 adult turtles (54.5%; SCL mean ± SD: 62.5 ± 2.0 cm, range: 60.0–66.3 cm) were females [ 38 , 39 ]. Subjective body condition assessments showed that two turtles (9.1%) were emaciated, four (18.2%) were thin, and 16 (72.7%) were in ‘good’ body condition.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 10 juvenile turtles (45.5%; SCL mean ± SD: 42.9 ± 12.6 cm, range: 26.7–59.0 cm), two were determined to be females based on visual examination of gonads at necropsy, and sex was undetermined in eight. The remaining 12 adult turtles (54.5%; SCL mean ± SD: 62.5 ± 2.0 cm, range: 60.0–66.3 cm) were females [ 38 , 39 ]. Subjective body condition assessments showed that two turtles (9.1%) were emaciated, four (18.2%) were thin, and 16 (72.7%) were in ‘good’ body condition.…”
Section: Resultsmentioning
confidence: 99%
“…Variation in the size of the adult testis could be caused by the environment. SCL could distinguish adults from juvenile Lepidochelys kempii sea turtles (Craven et al, 2019). It was expected that developmental variations in the turtle would be useful for phylogenetic studies and distinguishing the reproductive status of turtle species (Olukole et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings showed that testicular weight, testicular diameter, seminiferous tubule diameter, and spermatogenic cell count could be predicted based on the straight carapace length of the Indonesian box turtle (Cuora amboinensis couro). The correlation between SCL and testicular length and histology concluded that SCL was a significant predictor of the reproductive state of Kemp's Ridley Sea turtle (Lepidochelys kempii) (Craven et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, using this definition, some sexually mature animals using this definition may not reproduce effectively for several reasons: This could be due to behavioural mismatch or some other factor that prevents an individual from finding a mate, or the lack of resource capitalization during pre‐breeding migration if it is a capital breeder. Thus, a discrepancy in classification of sexual maturity is possible when based on the examination of the gonads in a dead stranded animal (Craven et al., 2019) or the observation of an animal nesting on a beach. Furthermore, the appearance of secondary sexual characteristics, such a long tail in male marine turtles, can be decoupled from functional sexual maturity (Casale et al., 2005).…”
Section: Introductionmentioning
confidence: 99%